'It's the brightness of the idea': Talking comics with Brendan McCarthy. Issue 1 (1st November 2021) - Klaehn, Jeffery
Visionary British artist and designer Brendan McCarthy is internationally known for his singularly unique approach to art and craft. His comics debut, Sometime Stories, was published in 1977, and he went on to publish work with Vanguard Illustrated, Strange Days, 2000 AD, and Vertigo. He was part of the famous 'British Invasion' of the comics industry in the 1980s, which actually led to the creation of DC Vertigo and created new pathways for comics to gain wider influence within both Hollywood and the broader pop culture. With writer Peter Milligan, he co-created Freakwave, Strange Days, Paradax!, Rogan Gosh and Skin, and he painted covers for Milligan's Shade the Changing Man DC Vertigo series. A pioneer in the field of computer animation, he created visuals for the 90s computer animated TV series ReBoot, which preceded Pixar and Dreamworks, and he contributed to a wide range of TV series, feature films, animation, and commercials during his more than two decades spent working in Hollywood. He co-wrote and was a designer on the feature film Mad Max: Fury Road (2015). His more recent comics work includes Dream Gang, published with Dark Horse, and The Zaucer of Zilk (with writer Al Ewing and colourist Len O'Grady) for 2000 AD. This interview explores key dimensions of his career in comics, British comics and the 'British Invasion' of the 1980s, Paradax!, and the influence and inspiration of David Bowie.